Spatial Characteristics of Permanent Relocation Housing in Disaster-Prone Areas of Cangkringan - Naufal, Muhamad Rafif; Nareswari, Ardhya (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
The Merapi relocation permanent residential settlements (huntap) are spread across 2 sub-districts, Cangkringan and Minggir. The relocation located in Disaster Prone Area (KRB) 2, an area with a high level of vulnerability. The settlements are in rural areas contoured by mountain slopes. This study aims to describe and identify the condition of the spatial character of huntap settlements from an accessibility perspective. Aspects that influence regional emergencies in the mitigation stage are the complexity of shelters, shelter buildings, land morphology, settlement accessibility and preservation facilities. This research was carried out qualitatively deductively with 18 objects of observation in the Merapi relocation huntap settlements. Data were collected from contour data (GIS-Google Earth), primary & secondary literature studies, observations and interviews. This classification is then analyzed based on physical characteristics in the form of buildings, land and preservation facilities. The character of the building  will influence the shape of the road pattern and the level of visibility. The morphological characteristics of the land  will influence the ease of mobility based on the shape of the road and human movement. The nature of preservation facilities will affect the level of wayfinding which residents can recognise their environment.. So to support the optimization of the success of the evacuation process, the main road is in a position parallel to the contour line, minimizing the potential for density accumulation. There is an open area between the grid so that the level of visibility is wider. Minimizing the number of intersections in areas that are segregated/separated from other areas. Adding access gates to the entrance and exit to prevent bottlenecks, accumulation in the gate area.. It is hoped that this study can be used as a reference, recommendation and basis for the government, architects, urban designers or planners in designing relocation shelters at other points.